DETERMINACIÓN DE ROTACIONES ÓPTIMAS EN LA APLICACIÓN DE RESALVEOS DE CONVERSIÓN A MONTE ALTO EN TALLARES DE ENCINA Y DE QUEJIGO EN LA ZONA CENTRAL DE LA PENÍNSULA IBÉRICA. - BRAVO, J A; Sánchez, I; Serrada, R (III Congreso Forestal Español, 2001)
Conversion thinning seems to be a good option for most of the coppicce forests of holm oak and gall oak, where the lack of management is causing severe problems. Intensity and rotation of thinning are the two main parameters to be studied. This paper deals with the second one. Six coppicce forests of holm oak and two for gall oak in the Guadalajara province where selected. Those stands had been thinned in a known date, and have been compared with near control stands, which have not been thinned in the past. Diameter growth after thinning has been studied throught rings count and ring width measurement in both kind of stands. 129 trees of holm oak and 79 trees of gall oak have been studied. The main conclusions are the evidence of a significant growth of diameter in holm oaks that is present 11 years after the thinning, while in gall oak results are not so clear. In gall oak just one site showed a positive answer to thinning, that was present until 17 years after. K.W.:
Keywords: conversion thinning; coppicce forest; gall oak; Growth; Holm oak; rotation

DETERMINACIÓN DE ROTACIONES ÓPTIMAS EN LA APLICACIÓN DE RESALVEOS DE CONVERSIÓN A MONTE ALTO EN TALLARES DE ENCINA Y DE QUEJIGO EN LA ZONA CENTRAL DE LA PENÍNSULA IBÉRICA. - BRAVO, J. A.; SÁNCHEZ, I.; SERRADA, R. (III Congreso Forestal Español, 2001)
Conversion thinning seems to be a good option for most of the coppicce forests of holm oak and gall oak, where the lack of management is causing severe problems. Intensity and rotation of thinning are the two main parameters to be studied. This paper deals with the second one. Six coppicce forests of holm oak and two for gall oak in the Guadalajara province where selected. Those stands had been thinned in a known date, and have been compared with near control stands, which have not been thinned in the past. Diameter growth after thinning has been studied throught rings count and ring width measurement in both kind of stands. 129 trees of holm oak and 79 trees of gall oak have been studied. The main conclusions are the evidence of a significant growth of diameter in holm oaks that is present 11 years after the thinning, while in gall oak results are not so clear. In gall oak just one site showed a positive answer to thinning, that was present until 17 years after. K.W.:
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español issue: 1 pub-location: Granada
Keywords: conversion thinning; coppicce forest; gall oak; Growth; Holm oak; rotation